Design and Realization of Teaching Demonstration System Based on .Net - Ailian Wang; Jinfei Ma; Yueming Qin (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In order to realize the systematic planning for teaching demonstration, this article proposed a teaching demonstration system based on .Net. The system adopted the techniques of Windows forms and serialization, Windows tree controls and the type and level of algorithm, component interface, advanced realization of windows graphics device interface, graphics drawing application programming interface, object link embedded, platform/assembly technology based on SOA, and was applied successfully in the development of the project, providing an effective method for informatization teaching. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2381